PETER PHAN: An MRI phantom for the optimisation of radiomic studies of the female pelvis. (March 2020) - Bianchini, Linda; Botta, Francesca; Origgi, Daniela; Rizzo, Stefania; Mariani, Manuel; Summers, Paul; García-Polo, Pablo; Cremonesi, Marta; Lascialfari, Alessandro
Highlights: The instructions to build the first MR radiomic phantom mimicking pelvis are given. The phantom reproduces the relaxation times of muscle and tumour tissue. It includes inserts that simulate the texture of representative pelvic tumours. It can be used to study the radiomic features stability in different MR settings. It is useful to optimise the radiomic workflow in MR. Abstract: Purpose: To develop a phantom for methodological radiomic investigation on Magnetic Resonance (MR) images of female patients affected by pelvic cancer. Methods: A pelvis-shaped container was filled with a MnCl2 solution reproducing the relaxation times (T1, T2 ) of muscle surrounding pelvic malignancies. Inserts simulating multi-textured lesions were embedded in the phantom. The relaxation times of muscle and tumour were measured on an MR scanner on healthy volunteers and patients; T1 and T2 of MnCl2 solutions were evaluated with a relaxometer to find the concentrations providing a match to in vivo relaxation times. Radiomic features were extracted from the phantom inserts and the patients' lesions. Their repeatability was assessed by multiple measurements. Results: Muscle T1 and T2 were 1128 (806–1378) and 51 (40–65) ms, respectively. The phantom reproduced in vivo values within 13% (T1 ) and 12% (T2 ). T1 and T2 of tumour tissue were 1637 (1396–2121) and 94 (79–101) ms, respectively. The phantom insert best mimicking the tumour agreed within 7% (T1 ) and 24% (T2 ) with in vivo values. Out of 1034 features, 75% (95%) had interclass correlation coefficient greater than 0.9 on T1 (T2 )-weighted images, reducing to 33% (25%) if the phantom was repositioned. The most repeatable features on phantom showed values in agreement with the features extracted from patients' lesions. Conclusions: We developed an MR phantom with inserts mimicking both relaxation times and texture of pelvic tumours. As exemplified with repeatability assessment, such phantom is useful to investigate features robustness and optimise the radiomic workflow on pelvic MR images.